THE DEVELOPMENT OF CARD MEDIA WITH SCIENTIFIC APPROACH ON JUNIOR HIGH SCHOOL OF MATHEMATICS LESSON - Erik Kuswanto; Imam Turmudi; Moh. Mahfud Effendi (MEJ (Mathematics Education Journal), 2017)
The goal of the research to describe of development of card media with scientificapproach on mathematics lesson, and show the practical and effectivity of cardmedia with scientific approach. The research's model use Borg and Gall model.The steps of the research are : analyze of potential and problem, the collect ofdata, product design, design validation and revision of design. Trying of test wasconducted to know the effectivity of card media. The instrument use observationsheet, questionnaire, and observation sheet of test's trying. The design of validation'sresult show that media is valid and it can apply on the teaching learning. Theresult of test's trying show that card media is practical to use as mathematicslearning's media. Beside that, the student classical of total's percentage after do thetest show that media is effective to use as teaching learning.